Sistem Pendukung Keputusan Rekomendasi Objek Wisata Di Kabupaten Berau Menggunakan Metode Fuzzy SAW - Suhantoro, Muhammad Wahyu (CV. Information Technology Training Center - Indonesia (ITTC), 2021)
Berau Regency is an administrative area in East Kalimantan Province. Berau Regency has been named the area with the most and most beautiful tourist attractions in East Kalimantan, both in terms of culinary, culture, customs, and even natural tourism. Of course this becomes a deja vu if there is no special tourism information system to determine decisions for choosing tourist attractions based on tourist backgrounds.In science there is a system called Fuzzy Multi Attribute Dicision Making (FMADM) or commonly known as; with Simple Additive Weighting (SAW). This system can be an option to get a solution for the selection of tourist attractions in Berau Regency. With this support system, it is hoped that it can help the Berau Regency Government in managing tourism in Berau Regency.In the decision to choose tourist attractions, it is necessary to classify the criteria needed by tourists as well as similar tourism alternatives. With the Fuzzy SAW method, it is expected to be able to help tourists to get information and recommendations for the desired tourist attractions in Berau Regency.The system of this method is useful for processing data on tourist criteria, until finally producing a recommendation of the expected tourist attractions. It is also hoped that this Decision Support System can help the Berau Regency Government, especially the Berau Regency Tourism and Culture Office.